Gender Differences in Chronic Obstructive Pulmonary Disease Symptom Clusters - Zhang H; Wu F; Yi H; Xu D; Jiang N; Li Y; Li M; Wang K (International Journal of COPD, 2021)
Haihong Zhang,1 Fang Wu,1 Hongli Yi,2 Dongjuan Xu,3 Nana Jiang,4 Yonghong Li,5 Ming Li,1 Kefang Wang1 1School of Nursing and Rehabilitation, Shandong University, Jinan City, Shandong Province, People’s Republic of China; 2Department of Respiratory Medicine, Shandong Provincial Hospital, Jinan City, Shandong Province, People’s Republic of China; 3School of Nursing, Purdue University, West Lafayette, IN, USA; 4Department of Respiratory Medicine, Dongfang Hospital Affiliated to Tongji University, Shanghai City, People’s Republic of China; 5Department of Respiratory Medicine, Jinan Central Hospital, Jinan City, Shandong Province, People’s Republic of ChinaCorrespondence: Ming LiSchool of Nursing and Rehabilitation, Shandong University, No.44 Wenhua Xi Road, Lixia District, Jinan City, Shandong Province, 250012, People’s Republic of ChinaTel +86-531-88382000Email liming74@sdu.edu.cnPurpose: Previous research has indicated that female and male patients may experience different levels of symptoms. However, no studies of chronic obstructive pulmonary disease (COPD) patients have compared the number and types of symptom clusters identified in male and female patients. Therefore, the purpose of this study was to investigate gender differences in symptom clusters among COPD patients.Patients and Methods: A total of 371 eligible patients were enrolled in the study. We assessed nine COPD symptoms, namely, dyspnea, cough, sputum, chest tightness, sleep quality, fatigue, frailty, anxiety, and depression. Exploratory factor analyses were used to explore the underlying clusters of the COPD symptoms.Results: Underlying the nine symptoms, female patients had 2 clusters, and male patients had 3 clusters. Specifically, the three general symptoms poor sleep, fatigue, and frailty loaded on the same symptom cluster with anxiety and depression in female patients, while the same 3 general symptoms loaded on the same symptom cluster with chest tightness and dyspnea in male patients. Moreover, cough and sputum not only were more common in male patients but also loaded together on a separate symptom cluster.Conclusion: Our findings suggest that in order to improve fatigue, frailty, and poor sleep quality, symptom management strategies should more closely address anxiety and depression in female patients as well as chest tightness and dyspnea in male patients. Smoking cessation is particularly important in male COPD patients because they account for a much higher proportion of smokers and are more likely to have cough and sputum. These findings signify the importance of identifying and implementing gender-tailored symptom management strategies to relieve symptom burden in COPD patients to enhance their quality of life.Keywords: quality of life, symptom burden, symptom management, factor analysis